2017
DOI: 10.1001/jamadermatol.2017.0202
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the Genotypic Spectrum of Bathing Suit Ichthyosis

Abstract: Bathing suit ichthyosis (BSI) is a rare congenital disorder of keratinization characterized by restriction of scale to sites of relatively higher temperature such as the trunk, with cooler areas remaining unaffected. Fewer than 40 cases have been reported in the literature. Bathing suit ichthyosis is caused by recessive, temperature-sensitive mutations in the transglutaminase-1 gene (TGM1). Clear genotype-phenotype correlations have been difficult to establish because several of the same TGM1 mutations have be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 23 publications
2
21
0
3
Order By: Relevance
“…This group, collectively designated as pleomorphic ichthyosis, consists of several clinically distinct conditions, including congenital ichthyosis with fine/mild scaling (CIFS), self‐improving collodion ichthyosis (SICI), and ichthyosis prematurity syndrome (IPS) (Bourrat, Blanchet‐Bardon, Derbois, Cure, & Fischer, ; Diociaiuti et al., ; Kiely, Devaney, Fischer, Lenane, & Irvine, ; Oji et al., ). Bathing‐suit ichthyosis (BSI), a condition in which arms and legs are not affected, has been defined as a minor variant of ichthyosis (Marukian et al., ). Other forms of ichthyosis include erythrokeratoderma variabilis, loricrin keratoderma, congenital reticular ichthyosiform erythroderma, and peeling skin syndrome (Mohamad et al., ; Oji et al., ; Youssefian, Touati, et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…This group, collectively designated as pleomorphic ichthyosis, consists of several clinically distinct conditions, including congenital ichthyosis with fine/mild scaling (CIFS), self‐improving collodion ichthyosis (SICI), and ichthyosis prematurity syndrome (IPS) (Bourrat, Blanchet‐Bardon, Derbois, Cure, & Fischer, ; Diociaiuti et al., ; Kiely, Devaney, Fischer, Lenane, & Irvine, ; Oji et al., ). Bathing‐suit ichthyosis (BSI), a condition in which arms and legs are not affected, has been defined as a minor variant of ichthyosis (Marukian et al., ). Other forms of ichthyosis include erythrokeratoderma variabilis, loricrin keratoderma, congenital reticular ichthyosiform erythroderma, and peeling skin syndrome (Mohamad et al., ; Oji et al., ; Youssefian, Touati, et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Our cases demonstrate the heterogeneity of BSI within the same family and even in the same individual across time. Patients with BSI are typically born with a widespread collodion membrane . Following shedding of the collodion membrane, large platelike scales develop and eventually persist in a unique “bathing suit” distribution.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, the homozygous variant has not been previously reported in BSI, although it is unambiguously pathogenic. In addition, a literature review of 54 BSI cases revealed multiple TGM1 variants that have been reported in both BSI and other subtypes of ARCI . These findings suggest that clear genotype‐phenotype correlations are difficult to establish due to the influence of genetic modifiers or epigenetics that alter gene expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First case was described in 1972 by Scott [2], followed by a case series by Jacyk, both from South Africa [3]. A current study by Marukian et al expanded the group of reported BSI cases by additional 9 new mutations in patients from different ethnic origins [4]. Altogether, the majority of BSI reports are from Africa, Europe, Turkey, Middle East, and China but no reports from India so far.…”
Section: Introductionmentioning
confidence: 96%